On Records : Delaware Indians, Colonists, and the Media of History and Memory - Newman, Andrew, 1968- (Book collections on Project MUSE., 2012)
Bridging the fields of indigenous, early American, memory, and media studies, On Records illuminates the problems of communication between cultures and across generations. Andrew Newman examines several controversial episodes in the historical narrative of the Delaware (Lenape) Indians, including the stories of their primordial migration to settle a homeland spanning the Delaware and Hudson Rivers, the arrival of the Dutch and the first colonial land fraud, William Penn's founding of Pennsylvania with a Great Treaty of Peace, and the infamous 1737 Pennsylvania Walking Purchase. Newman demonstrates that the quest for ideal records--authentic, authoritative, and objective, anchored in the past yet intelligible to the present--has haunted historical actors and scholars alike. Yet without "proof," how can we know what really happened? On Records articulates surprising connections among colonial documents, recorded oral traditions, material and visual cultures. Its comprehensive, probing analysis of historical evidence yields a multi-faceted understanding of events and reveals new insights into the divergent memories of a shared past.